2021
DOI: 10.1002/pros.24117
|View full text |Cite
|
Sign up to set email alerts
|

Periprostatic adipose tissue promotes prostate cancer resistance to docetaxel by paracrine IGF‐1 upregulation of TUBB2B beta‐tubulin isoform

Abstract: Growing evidence supports the pivotal role played by periprostatic adipose tissue (PPAT) in prostate cancer (PCa) microenvironment. We investigated whether PPAT can affect response to Docetaxel (DCTX) and the mechanisms associated. Conditioned medium was collected from the in vitro differentiated adipocytes isolated from PPAT which was isolated from PCa patients, during radical prostatectomy. Drug efficacy was studied by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide citotoxicity assay. Culture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…In addition to KMT2B , we also found several other gene candidates on HBV‐related GC for further studies. TUBB2B and FGF12 have been suggested to play vital functions in prostate cancer ( Liotti et al., 2021 ), neuroblastoma ( Zafar et al., 2021 ), and esophageal squamous cell carcinoma ( Bhushan et al., 2017 ); however, their roles in HBV-related GC development have never been documented and merit further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to KMT2B , we also found several other gene candidates on HBV‐related GC for further studies. TUBB2B and FGF12 have been suggested to play vital functions in prostate cancer ( Liotti et al., 2021 ), neuroblastoma ( Zafar et al., 2021 ), and esophageal squamous cell carcinoma ( Bhushan et al., 2017 ); however, their roles in HBV-related GC development have never been documented and merit further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, it could be informative to investigate the effect of PPAT-released factors on the PCa cell aggressive phenotype. We previously demonstrated that adipose tissue-released IGF-1 contributed to docetaxel resistance of PCa cells [ 15 ]. In addition, the ability of adipocyte secretome to promote metastatic expansion has been clearly demonstrated in breast cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Western blot assays, cells were washed with ice-cold phosphate-buffered saline (PBS) and harvested in a Laemmli buffer (with β-mercaptoethanol) containing a mixture of phosphatase inhibitors (0.5 mM sodium vanadate, 2 mM sodium pyrophosphate, 5 mM β-glycerolphosphate, and 50 mM sodium fluoride) and the protease inhibitor phenylmethylsulfonyl fluoride (Sigma–Aldrich). Western blots were carried out as previously reported [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, an under-studied AT that is particularly pertinent to the etiology of PCa is the periprostatic adipose tissue (PPAT) that is situated in the proximity of the prostate [ 17 ]. Indeed, PPAT dysfunction and inflammation not only amplify rudimentary neoplastic alterations of the healthy prostate, but also promote PCa progression, metastasis, and resistance to chemotherapy [ 17 , 18 , 19 , 20 , 21 , 22 ]. Compared to other adipose depots, the cellular and molecular heterogeneity as well as the thermogenic potential of PPAT remain largely uninvestigated.…”
Section: Introductionmentioning
confidence: 99%